The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18510/hssr.2020.83142
|View full text |Cite
|
Sign up to set email alerts
|

Employers Perception on Graduate Skill Deficiency to Suit Productivity

Abstract: Purpose of the study: This study aims to investigate the perception of employers on the skill deficiency of graduates. The study also attempts to explore the nature and importance of employability skills with emphasis on the areas of deficiency that could be addressed by higher education institutions (H.E.I.s) to make their graduates more employable. Methodology: This paper is a theoretical exploration based on existing literature. Relevant research papers were sourced from prominent online databases, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Bano and Vasantha (2019) found that personal abilities like working independently, creativity and innovation, adaptability, integrity, loyalty, versatility and resilience; were considered as important as generic and domain-specific skills. These skills were important during the pandemic, wherein personal attitude and behavior at work became more emphatic (Soundararajan et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bano and Vasantha (2019) found that personal abilities like working independently, creativity and innovation, adaptability, integrity, loyalty, versatility and resilience; were considered as important as generic and domain-specific skills. These skills were important during the pandemic, wherein personal attitude and behavior at work became more emphatic (Soundararajan et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Studies highlight the need for ongoing collaboration with industry partners. 41,[43][44][45] This implies that collaboration can help identify and address any discrepancies between the curriculum and workplace requirements.…”
Section: Dovepressmentioning
confidence: 99%
“…These findings reflect that the industry emphasized document processing and hardware operation and maintenance skills. Further, the prospective employers claimed that fresh graduates were lacking with required skills related to the job [26], [27]. Despite of positive declined in graduate unemployment rate from 4.4% in 2020 to 4.1% in 2020, yet, there is an increased in semi-skilled and lowskilled job categories in the labor market from 31.2% in 2020 to 33.9% in 2021 [28].…”
Section: Introductionmentioning
confidence: 99%